2022
DOI: 10.3390/life12101528
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanol in Maternal or Neonatal Blood to Detect Alcohol Exposure during Pregnancy: A Systematic Review

Abstract: Background: Alcohol consumption during pregnancy, even at low doses, may damage the fetus. Pregnant women tend to underreport their alcohol consumption generating the need for sensitive and specific biomarkers, among which PEth has emerged due to its high specificity and possibility to be measured in both maternal and neonatal blood. The aim of this study is to systematically review the latest 20 years of literature for depicting the state of the art, the limitations, and the prospects of PEth for estimating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Through metabonomic analysis of the changes in the body caused by AUD or alcohol dependence, some trait or state markers are found; these provide very important objective biomarkers for forensic and clinical toxicology [75,76]. For example, phosphatidylethanol is a promising marker for monitoring alcohol use in pregnancy [77], while salivary exoglycosidases and deglycosylation processes can be biochemical markers for chronic alcohol consumption and dependence [78].…”
Section: Metabolomics In Aud/ptsdmentioning
confidence: 99%
“…Through metabonomic analysis of the changes in the body caused by AUD or alcohol dependence, some trait or state markers are found; these provide very important objective biomarkers for forensic and clinical toxicology [75,76]. For example, phosphatidylethanol is a promising marker for monitoring alcohol use in pregnancy [77], while salivary exoglycosidases and deglycosylation processes can be biochemical markers for chronic alcohol consumption and dependence [78].…”
Section: Metabolomics In Aud/ptsdmentioning
confidence: 99%
“…Phosphatidylethanol (PEth), a phospholipid formed in the presence of ethanol, may be detected in maternal blood up to 6 weeks after low to moderate alcohol consumption and can be used to confirm maternal alcohol use in blood from the fetus when in doubt of, i.e., diagnoses 36 . A review from 2022 concluded that PEth has higher sensitivity than selfreported alcohol consumption, but further studies are needed 37 . Fatty acid ethyl esters (FAEEs) measured in meconium have also been argued to be more sensitive than selfreports 38 , and Ethyl glucuronide (EtG) and FAEEs have been suggested to be admissible for clinical use in the detection of PAE 39 .…”
Section: Assessment Of Alcoholmentioning
confidence: 99%